Effect of rhodium doping for photocatalytic activity of barium titanate - Kaptagay, G.A.; Satanova, B.M.; Abuova, A.U.; Konuhova, Marina; Zakiyeva, Zh.Ye.; Tolegen, U. Zh; Koilyk, N.O.; Abuova, F.U. (Elsevier B.V., 2025)
By means of DFT oxygen evolution reaction on Rh-doped BaTiO3 (001) surface has been modeled. Gibbs free energies for each step of the reaction as well as the values of overpotential have been calculated, taking into account the solvation effect. The position of Rh-induces defect energy levels have been determined. Our findings indicated a substantial reduction in overpotential for the Rhodium-modified TiO2 surface compared to the bare surface. The high overpotential on the bare BaTiO3 surface suggests low OER efficiency, making Rh doping a promising strategy for enhancement. © 2024 The Author(s) --//-- This is an open-access article G.A. Kaptagay, B.M. Satanova, A.U. Abuova, M. Konuhova, Zh.Ye. Zakiyeva, U. Zh Tolegen, N.O. Koilyk, F.U. Abuova, Effect of rhodium doping for photocatalytic activity of barium titanate, Optical Materials: X, Volume 25, 2025, 100382, ISSN 2590-1478, https://doi.org/10.1016/j.omx.2024.100382.
This work was supported by the Ministry of Science and Higher Education of the Republic of Kazakhstan, grant number IRN AP14972859. Institute of Solid State Physics, University of Latvia, as the Center of Excellence, has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Electrocatalysis; Electrode materials; Energy storage and conversion; Photocatalysis; Water splitting